An Overview of the Correlation between Societal Influences, Bodybuilding, and Muscular Dysmorphia - Quinn, Aidan (Kansas State University. K-State Libraries, 2022)
Data suggests that there is an underlying connection between societal influences (i.e. childhood, advertisements), bodybuilding training, and muscular dysmorphia, a condition in which a patient believes they are "too small." This relationship is discussed and explored in this literature review.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: societal influences; bodybuilding; muscular dysmorphia; body image; literature review